Post-colonoscopy colorectal cancer: Evaluation of a cohort in its clinical and colonoscopic characteristics, survival and its causes according to the World Endoscopy Organization - Castaño-Llano, Rodrigo (2023)
Post-colonoscopy colorectal cancer (PCCRC) is a tumor that appears after a normal colonoscopy before the established time for the endoscopic follow up. Its origin reflects the quality of the colonoscopy and the different tumoral biologics between the CRC and the CRCPC. Our aim is to describe the characteristics of the PCCRC in our region, to identify risk factors, to discriminate the potential causes according to the World Endoscopý Organization (WEO) and to determine its impact in the patient’s survival. We studied patients with colorectalcancer (CRC) attended at the gastro-oncology clinic of two institutions of Medellin-Colombia, between January 2012 and December 2021 that had been submitted to a colonoscopy between 6-36 months before the colonoscopy in which the CRC was diagnosed. 919 patients during 10 years for CRC, 68 cases of PCCRC (6.9%); It was more frequent in older patients (74 vs. 66 years; p=0.03), with background of adenomatous polyps (36.8% vs. 20.1%; p=0.01) and in right colon (57.4% vs. 40.6%; p=0.006), with a tendency in patients with diverticulosis (41.2% vs. 31.3%; p=0.05) and diabetes (25% vs. 14%; p=0.06); less survival at 5 and 10 years (58% and 55.2% vs. 67% and 63%; p<0.001). According to the WEO, the PCCRC presents in 61.3% because of abnormal findings omitted in inadequate colonoscopies, 29% in a suitable colonoscopy and 9.7% incomplete resections of adenomas. In conclusion, the rate of PCCRC was 6.9% with more propension in older patients, a background of polyp resection, and proximal colon. According to the WEO, the abnormal findings omitted more frequently were related with inadequate colonoscopies. The patients with PCCRC had less survival.